Prevalensi dan persepsi disfagia pada populasi lanjut usia di Kota Denpasar periode September-Desember 2021 - I Putu Santhi Dewantara; I Wayan Sucipta (Intisari Sains Medis, 2021)
Background: To investigate prevalence and perception of dysphagia in Denpasar City. The causes of dysphagia in the elderly include changes in the function and structure of the organs involved in the swallowing process, which are multifactorial. Dysphagia does affect not only the health aspect of the sufferer but also the social and economic aspects, especially in the elderly population. This study aims to determine the prevalence and perception of dysphagia in the elderly in Denpasar City.Methods: This is a descriptive cross-sectional study that obtains data from the public health center in Denpasar City. Dysphagia was detected using the Swallowing Disturbances Questionaire (SDQ) and perception of dysphagia was obtained using direct questions. Data were analyzed using SPSS version 21 for Windows.Results: 102 samples were obtained, with the most gender being female (61.75%), and the age group was 60-69 years old (68.63%). A total of 11.76% of the sample stated that they had swallowing difficulties, while based on SDQ 10.78% had dysphagia. The most common comorbidities in the dysphagia group were head and neck malignancy (27.7%) and hypertension (27.7%), while in the non-dysphagic group were joint and skeletal disorders (34.09%).Conclusion: The prevalence of dysphagia in the elderly in Denpasar City is quite high, 10.78% based on SDQ and 11.76% based on the direct question. This requires special attention to overcome or prevent problems that may arise from dysphagia in the elderly. Latar Belakang: Disfagia diartikan sebagai gangguan menelan saliva, makanan padat dan cair, termasuk obat-obatan. Penyebab disfagia pada lansia diantaranya adalah perubahan fungsi dan struktur organ yang terlibat dalam proses menelan yang bersifat multifaktorial. Disfagia tidak hanya mempengaruhi aspek kesehatan penderitanya, namun juga aspek sosial dan ekonominya terutama pada populasi lanjut usia. Penelitian ini bertujuan untuk mengetahui prevalensi dan persepsi  disfagia pada lanjut usia di Kota Denpasar.Metode: Penelitian ini menggunakan rancangan penelitian deskriptif potong lintang dengan mengambil data di puskesmas-puskesmas kota Denpasar menggunakan kuisioner. Disfagia dideteksi menggunakan Swallowing Disturbances Questionnaire (SDQ) sedangkan persepsi disfagia didapatkan dengan pertanyaan langsung. Data dianalisis dengan SPSS versi 21 untuk WindoesHasil: Didapatkan sampel sebanyak 102 orang, dengan jenis kelamin terbanyak adalah perempuan (61,75%) dan rentang usia 60-69 tahun (68,63%). Sebanyak 11,76% menyatakan mengalami gangguan menelan, sedangkan berdasarkan SDQ didapatkan 10,78% mengalami disfagia. Penyakit penyerta terbanyak pada kelompok disfagia adalah keganasan kepala leher (27,27%) dan hipertensi (27,27%). Sedangkan pada kelompok tidak disfagia adalah gangguan sendi dan tulang (34,09%).Kesimpulan: Prevalensi disfagia pada populasi lansia di Kota Denpasar cukup tinggi. Hal ini memerlukan perhatian khusus untuk mengatasi dan mencegah permasalahan yang dapat timbul akibat disfagia pada lansia.